Peach pies and alibis eaudiobook - Adams, Ellery (Charmed Pie Shoppe Mystery, 2016)
Ella Mae LeFaye's Charmed Pie Shoppe is wildly popular in Havenwood, Georgia, which is not surprising since Ella Mae can lace her baked goods with enchantments. The shop's extraordinary success seems destined to continue when Ella Mae meets an engaged couple who hire her to handle the dessert buffet at their wedding. But Ella Mae has a lot on her plate. She is also searching for the origin of her magical powers, and hoping to determine if the spark of attraction she feels for the handsome Hugh Dylan is authentic or just her new abilities gone awry. Then Ella Mae discovers a high-standing member of the community dead, and a wedding guest becomes seriously ill at the event she's catering. Now she'll have to use all her sleuthing skills and culinary talents to prove that her pies don't contain a killer ingredient.